AKTIVITAS ANTIOKSIDAN METABOLIT SEKUNDER Sporothrix sp. LBKURCC43 YANG DIISOLASI DARI TANAMAN DAHLIA (Dahlia variabilis) - siti rahmah (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2016)
Fungus Sporothrix sp. LBKURCC43 is one of fungi which has been succeded to be isolated from Dahlia tuber (Dahlia variabilis). This reseach aimed to produce secondary metabolytes and antioxidant activity secondary metabolytes of fungus Sporothrix sp. LBKURCC43 in Huang medium. Measurement of antioxidant activity on secondary metabolytes were analyzed by DPPH (2,2-diphenyl-1-picryl-hydrazyl) showed the highest activity was found in 20th day secondary metabolytes in Huang medium with IC50 828,614 μg/mL.